Environmental Education Factor Affecting Waste Management Behavior of Villager - Lhaophet, Napaporn (วารสารวิชาการมหาวิทยาลัยอีสเทิร์นเอเชีย ฉบับวิทยาศาสตร์และเทคโนโลยี (online), 2016)
The survey research objectives were to study knowledge, awareness, participation of waste management, and waste management behavior levels, and effects of independent variables comprising of knowledge, awareness and participation of waste management affecting waste management behavior. The survey research questionnaires were conducted to collect 299 people of Ban Kanhug, Si Kaew Sub-district, Muang District, Roi-et Province. Multiple Regression Analysis was used to determine the relationship between independent variables and dependent variable. The findings illustrated that in holistic view of study knowledge, awareness, participation of waste management, and waste management behavior were at most level in all aspects. Moreover, independent variables of knowledge, awareness, participation of waste management, environmental conservation inspiration with public mind affected to dependent variable of waste management behavior of community people with 64.30 percents of power prediction (Adjusted R2 = 0.643). The knowledge of waste management was the highest effect with 0.395 and subsequence was participation with 0.313.Recommendation of the research, the knowledge and participation of waste management are the most important factor to affect to waste management behavior. Therefore, the local administrative organization should hold the activities to give knowledge and persuade villagers to gain more knowledge and participate to join waste management in village.